Impact of referral letters on scheduling of hospital appointments: a randomised control trial - Jiwa, Moyez; Meng, Xingqiong (Rosie); O'Shea, C.; Magin, P.; Dadich, A.; Pillai, V. (Royal College of General Practitioners, 2014)
Background: Communication is essential for triage, but intervention trials to improve it are scarce. Referral Writer (RW), a referral letter software program, enables documentation of clinical data and extracts relevant patient details from clinical software.Aim: To evaluate whether specialists are more confident about scheduling appointments when they receive more information in referral letters. Design and setting Single-blind, parallel-groups, controlled design with a 1:1 randomisation. Australian GPs watched video vignettes virtually. Method: GPs wrote referral letters after watching vignettes of patients with cancer symptoms. Letter content was scored against a benchmark. The proportions of referral letters triagable by a specialist with confidence, and in which the specialist was confident the patient had potentially life-limiting pathology were determined. Categorical outcomes were tested with χ2 and continuous outcomes with t-tests. A random-effects logistic model assessed the influence of group randomisation (RW versus control), GP demographics, clinical specialty, and specialist referral assessor on specialist confidence in the information provided. Results: The intervention (RW) group referred more patients and scored significantly higher on information relayed (mean difference 21.6 [95% confidence intervals CI = 20.1 to 23.2]). There was no difference in the proportion of letters for which specialists were confident they had sufficient information for appointment scheduling (RW 77.7% versus control 80.6%, P = 0.16). In the logistic model, limited agreement among specialists contributed substantially to the observed differences in appointment scheduling (P = 35% [95% CI 16% to 59%]). Conclusion: In isolation, referral letter templates are unlikely to improve the scheduling of specialist appointments, even when more information is relayed.